Impact of Nano-FeS2 Layer on the Stability Performance of CdS-Cu2O PV Cells: A Study - Ghosh, Biswajit (Journal of Basic & Applied Sciences, 2021)
The presence of nano-structured FeS2 film at the junction of CdS-Cu2O thin film PV cells demonstrated long term stability in its performances. The CdS layer was fabricated by vacuum evaporation technique and its top surface was converted to FeS2 by dipping in hot FeCl2 solution. The Cu2O was deposited over it by plasma deposition process. A thin Ni-Au layer was deposited over the Cu2O surface by an electroless deposition process to act as the top electrical contact. The cell properties and its stability were studied under external stresses including heat and light. The cells efficiency attained 2.35% at AM1 illumination. The fabricated cells were tested under thermal cycling and light soaking and their performances were compared with other cells like Si, CdTe and CIS. Results showed that the CdS-Cu2O device with FeS2 is more stable than the other cells. From these results it was concluded that the nano FeS2 layer made perfect matching with n-CdS and p-Cu2O due to its strong inversion and yields both bulk electrons and surface holes. Moreover, the hardness of the FeS2 layer puts barriers that slow the inter-diffusion / migration of Cu ions into the bulk CdS thus preventing the formation of Cu-Cd killer centres.